Mulk Raj Anand’s Vision of Social Injustice and Exploitation in the Light of Gandhian Thought: Exploring the Influence of Gandhian Thought on Mulk Raj Anand's Portrayal of Social Injustice (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Anand, as is well known, was under a great and direct influence of Mahatma Gandhi. He felt immense pity for the down-trodden class who were the innocent victims of social injustice and exploitation. Gandhi devoted his life for the uplift of the same class and Anand followed his path at least in literature.